King of Cyprus Peter I Lusignan: From Hero to Tyrant and Back - Svetlana Vladimirovna Bliznyuk (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2022)
In this article, the author deals with the Cypriot society’s process of reflection regarding the life and death of the legendary king Peter I Lusignan of Cyprus (1359–1369). In world historiography, many works are devoted to his life and acts. The originality of this research lies in an innovative articulation of the issue, i.e. an attempt to understand the process of the victorious king’s transformation into a tyrant hated by everybody and then back into a hero. The author deals with the deeds of the king as a politician and crusader only to the extent that is necessary to explain the above processes. Peter I Lusignan could show his best side and impress others. If his policies were successful, he remained a courteous and glorious king. As soon as his domestic and foreign policy was defeated, the negative sides of his psyche came to the forefront. His tyranny became so unbearable that to his vassals his death seemed the only way to save themselves and the kingdom. However, then the Cypriot society reframes the murder as a moral sin, the penalty for which lies on all Cypriots, without exception. The society repents for the assassination. All the subsequent political, social, and economic hardships of the kingdom are explained through the prism of the sin of killing the king. The Cypriot society identifies itself with his great victories, his glory, and his greatness. His victorious crusades are recognised as part of the history of the Kingdom of Cyprus. This helps to bring Peter I Lusignan back as a victorious hero in historical memory.